Association of sleep characteristics with cardiovascular disease risk in adults over 40 years of age: a cross-sectional survey - Hou, Xin-Zheng; Li, Yu-Shan; Wu, Qian; Lv, Qian-Yu; Yang, Ying-Tian; Li, Lan-Lan; Ye, Xue-Jiao; Yang, Chen-Yan; Wang, Man-Shi; Lv, Yan-Fei; Cao, Lin-Lin; Wang, Shi-Han (Frontiers in Cardiovascular Medicine, 2024)
The relationship between sleep characteristics and cardiovascular disease (CVD) risk has yet to reach a consistent conclusion, and more research needs to be carried out. This study aimed to explore the relationship between snoring, daytime sleepiness, bedtime, sleep duration, and high-risk sleep patterns with CVD risk.: Data from the National Health and Nutrition Examination Survey (NHANES) 2015-2018 were collected and analyzed. Multivariable logistic regression was used to evaluate the relationship between snoring, daytime sleepiness, bedtime, sleep duration, high-risk sleep patterns, and CVD risk. Stratified analysis and interaction tests were carried out according to hypertension, diabetes and age. Results: The final analysis contained 6830 participants, including 1001 with CVD. Multivariable logistic regression suggested that the relationship between snoring [OR=7.37,95%CI=(6.06,8.96)], daytime sleepiness [OR=11.21,95%CI=(9.60,13.08)], sleep duration shorter than 7 hours [OR=9 .50,95%CI=(7.65,11.79)] or longer than 8 hours [OR=6.61,95%CI=(5.33,8.19)], bedtime after 0:00 [OR=13.20,95%CI=(9.78,17.80)] compared to 22:00-22:59, high-risk sleep patterns [OR=47. 73,95%CI=(36.73,62.04)] and CVD risk were statistically significant. Hypertension and diabetes interacted with high-risk sleep patterns, but age did not.Conclusions: Snoring, daytime sleepiness, excessive or short sleep duration, inappropriate bedtime, and high-risk sleep patterns composed of these factors are associated with the CVD risk. High-risk sleep patterns have a more significant impact on patients with hypertension and diabetes.